Infection with Mycobacterium ulcerans induces persistent inflammatory responses in mice - Oliveira, Martinha S. (2005)
Buruli ulcer (BU) is a devastating, necrotizing, tropical skin disease caused by infections with Mycobacterium ulcerans. In contrast to other mycobacterioses, BU has been associated with minimal or absent inflammation. However, here we show that in the mouse M. ulcerans induces persistent inflammatory responses with viru-lence- dependent patterns. Mycolactone-positive, cytotoxic strains are virulent for mice and multiply progres-sively, inducing both early and persistent acute inflammatory responses. The cytotoxicity of these strains leads to progressive destruction of the inflammatory infiltrates by postapoptotic secondary necrosis, generating necrotic acellular areas with extracellular bacilli released by the lysis of infected phagocytes. The necrotic areas, always surrounded by acute inflammatory infiltrates, expand through the progressive invasion of healthy tissues around the initial necrotic lesions by bacteria and by newly recruited acute inflammatory cells. Our observations show that the lack of inflammatory infiltrates in the extensive areas of necrosis seen in advanced infections results from the destruction of continuously produced inflammatory infiltrates and not from M. ulcerans-induced local or systemic immunosuppression. Whether this is the mechanism behind the predomi-nance of minimal or absent inflammatory responses in BU biopsies remains to be elucidated.